The Influence of Influencer Marketing and Product Quality on Purchase Decisions at The Don’s House in Bandar Lampung - Prisilia, Riris; Riswan (Journal of Advances in Accounting, Economics, and Management, 2025)
Social media serves as both a communication platform and a promotional tool, with influencer marketing playing a key role. At The Don’s House in Bandar Lampung, local influencers significantly increased Insta Story views to over 300,000, highlighting their impact on brand promotion. Product quality is crucial in shaping purchase decisions, as high-quality products enhance customer satisfaction and loyalty. This study examines the combined influence of influencer marketing and product quality on purchase decisions at The Don’s House. Data were collected through questionnaires and customer interviews and analysed using quantitative methods. The results indicate that both influencer marketing and product quality, individually and collectively, positively and significantly affect purchase decisions.